2022
DOI: 10.1088/2515-7655/ac8ed3
|View full text |Cite
|
Sign up to set email alerts
|

Critical factors for photoelectrochemical and photocatalytic H2 evolution from gray anatase (001) nanosheets

Abstract: In recent years, defect engineering of titania via reduction treatments has shown a high promise for enabling efficient and co-catalyst-free photocatalytic H2 generation from methanol/water solutions. However defect engineering alters several properties of TiO2 simultaneously. Here we use pristine (white) and hydrogenated (grey) anatase nanosheets with dominant (001) facets and by comparing electrical conductivity, photocurrent spectra, transient photocurrent response, and photocatalytic H2 evolution, we show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Consequently, the three forms of titania herein studied exhibit different density and nature of oxygen vacancies (Ti 3+ -O V ) and, thus, different electronic properties . We characterized these materials in view of their electronic and defect structure in previous work. ,, Unlike low temperature treatments (e.g., 500 °C) that maintain anatase as the only crystalline phase, hydrogenation at 700 °C (to form the over-reduced black TiO 2 ) results in a mixed anatase–rutile composition . Among different “shades” of gray titania, i.e., thermally treated in H 2 at different reduction temperatures (300–700 °C), the powder treated at 500 °C for 1 h ( gray TiO 2 ) shows the highest photocatalytic activity (shown in our previous work).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the three forms of titania herein studied exhibit different density and nature of oxygen vacancies (Ti 3+ -O V ) and, thus, different electronic properties . We characterized these materials in view of their electronic and defect structure in previous work. ,, Unlike low temperature treatments (e.g., 500 °C) that maintain anatase as the only crystalline phase, hydrogenation at 700 °C (to form the over-reduced black TiO 2 ) results in a mixed anatase–rutile composition . Among different “shades” of gray titania, i.e., thermally treated in H 2 at different reduction temperatures (300–700 °C), the powder treated at 500 °C for 1 h ( gray TiO 2 ) shows the highest photocatalytic activity (shown in our previous work).…”
Section: Resultsmentioning
confidence: 99%
“…However, the surface amorphization become a matter of debate. For example, titania commercial powders with a rather rough surface exhibit surface amorphization, while single crystals [3,12] and hydrothermal powders with well‐defined facets do not exhibit, but only point defect formation [13] . Additionally, it was confirmed that different titania polymorphs show varied behaviors towards reductive treatments, i. e., brookite is more readily reduced compared to anatase and rutile [3] .…”
Section: Introductionmentioning
confidence: 92%
“…The dynamics of these photo-excited charge carriers are typically studied using techniques like time-resolved photoluminescence (TP), 40–45 transient absorption (TA), 20,33,45–58 and time-resolved microwave conductivity (TMC). 59,60 TP is sensitive to the emission of excited carriers but overlooks non-emissive processes.…”
Section: Introductionmentioning
confidence: 99%
“…38 In the process of water splitting in hematite charge carriers show a non-exponential decay with long lifetimes, which are dependent on the applied bias voltage. 39 The dynamics of these photo-excited charge carriers are typically studied using techniques like time-resolved photoluminescence (TP), [40][41][42][43][44][45] transient absorption (TA), 20,33,[45][46][47][48][49][50][51][52][53][54][55][56][57][58] and time-resolved microwave conductivity (TMC). 59,60 TP is sensitive to the emission of excited carriers but overlooks non-emissive processes.…”
Section: Introductionmentioning
confidence: 99%